Signs of oral dryness in relation to salivary flow rate, pH, buffering capacity and dry mouth complaints - Farsi Najat MA (BMC, 2007)
Abstract Background This study aimed to investigate the signs of oral dryness in relation to different salivary variables and to correlate subjective complaints of oral dryness with salivary flow rate. Methods 312 unmedicated healthy individuals belonging to three age groups, (6-11, 12-17, and 18-40 years) were examined clinically for signs of oral dryness. Resting and stimulated saliva were collected to determine flow rate, pH and buffering capacity. A questionnaire was used to obtain information on subjective sensation of dry mouth. Results Dry lip and dry mucosa were present in 37.5% and 3.2% of the sample respectively. The proportion of subjects who complained of oral dryness (19%) showed a stimulated salivary flow rate significantly lower than non complainers. Dry lip was significantly related to low resting flow rate but pH and buffering capacity did not show any significant relation to dry lip. Dry mucosa was not related to any of the above mentioned parameters. Conclusion The finding that the stimulated salivary flow rate was reduced in subjects complaining of dry mouth is of great clinical relevance, since the reduction is expected to be reflected in compromising various salivary functions.